(untitled) (Journal of Philosophy, Culture and Political Science, 2016)
This article examines the Canadian experience of building a multicultural society. Canada has long been called the country a «cultural mosaic», due to the fact that it is made up of a diverse mix of races, cultures and ethnicities. For the first time in the world, in this country, multiculturalism – as a political ideology, became formally recognized at the state level. Despite some challenges, with respect to the integration of migrants and the French-speaking Quebec as a whole, the Canadian model of multiculturalism can be regarded as the most successful.